The Boundless - Oppel, Kenneth, 1967- (Simon & Schuster Books for Young Readers, 2015)
Aboard "The Boundless," the greatest train ever built, on its maiden voyage across Canada, teenaged Will enlists the aid of a traveling circus to save the train from villains.